A conductor's analysis of Charles Carter's Overture for Winds - Wynja, Arjen S., author; Phillips, Rebecca, advisor; Taylor, Jayme, committee member; Herman, Christina, committee member (Colorado State University. Libraries, 2025)
The senior thesis is a capstone project submitted in partial fulfillment of the requirements for the Colorado State University Honors Program. To make this project relevant to my undergraduate degree in music education and future career, I choose to study the large ensemble rehearsal process. My advisor is Dr. Rebecca Phillips, Director of Bands at Colorado State University, and a former secondary school band director. Other committee members are Dr. Jayme Taylor and Dr. Christina Herman. The subject work of the thesis is Charles Carter's Overture for Winds, and the project contains the following exercises: a written conductor's analysis, meetings with Dr. Phillips throughout the term, and rehearsal and festival performance of Overture for Winds with the Fossil Ridge High School (FRHS) Symphonic Band. The performance is at the Rocky Mountain HS Concert Band Festival on November 20. The purpose of this project is to practice the process of detailed score study, learn how this study, in turn, allows for efficient rehearsal, and how the efficient rehearsal provides a platform for a successful performance for students. Additionally, this project will prepare me for larger scale works in graduate school. The score study and rehearsal process is a foundational skill that will serve me throughout my career. Finally, this analysis of Charles Carter's Overture for Winds will serve as a helpful resource for other conductors in their preparation of the work. The body of this thesis consists of two main sections. Section One is a biographical sketch about Charles Carter and analysis of his compositional voice, and Section Two is a theoretical and rehearsal analysis of Overture for Winds. In Section One, the biographical sketch discusses Carter’s early life, teachers and influences, major career phases, and relevant historical context. I also examine Carter's compositional voice through the elements of music, including form, melody, harmony, tonality, texture, rhythm/tempo, and orchestration, how he uses them in his music, and how this compares to the work of his contemporaries. Section Two is a theoretical and rehearsal analysis which covers all notable elements of music in each section of the work, ordered chronologically. The theoretical analysis explores Carter's use of the elements of music in the construction of the piece, while the accompanying rehearsal analysis discusses how a conductor might apply this content with their ensemble. This includes technical considerations, orchestration challenges, and other items covered in rehearsal. Musical figures and tables are used as needed.
Keywords: music; music education; conducting; conductor's analysis; Carter, Charles; wind band; concert band; symphonic band; band director